The Effect of Brain-Compatible Strategies on Problem Solving Performance of Grade 4 and 5 Lebanese Students - Shukry-Balaa, Rola; El-Hassan, Karma (European Scientific Journal, ESJ, 2018)
This study investigated the effect of training in Prior Knowledge Activation, Concept Mapping, and Think Aloud, on students’ problem solving performance. The relative effectiveness of the training among high and low achievers was also examined. Participants were 45 students in Grades 4 and 5 in two private schools in Lebanon (25 students experimental group; 20 as control). The experimental group received 3 weeks training, in addition to the regular methods while the control received the regular methods only. Curriculum-based assessments (reading comprehension and math word problem solving) and Raven’s Colored Progressive Matrices, were used to measure problem solving performance. ANCOVA results showed a significant difference in experimental and control groups’ posttest scores, in favor of the experimental group. ANOVA results showed that the mean differences between pre and post test scores of low and high achieving students in the experimental group differed significantly only on math word problem solving measure, in favor of the low achievers. Results are discussed and implications and future recommendations are presented.